Cases Study: Evaluation of Student Readyness in Teaching After Microteaching - Entin Daningsih (Bioeducation Journal, 2021)
Capability to teach is expected to have by Biology Education students after having Microteaching. Case study was conducted to evaluate how teaching performance of students from the start to the end of microteaching. Research samples were 6 students of Biology Education Study at 6th semester. microteaching was done online and offline. Eight skills was firstly conducted online step by step. Each performance was evaluated by other students and written in log book. Evaluation was used to improve each performance. Microteaching was continuedly offline in which students must performe teaching three times, two with supervision dan one independenly. Improvement had given for a better performance supervised for opening to closure of teaching. Results from online and offline training was implemented in independent teaching performance for 30 minutes. Teaching performance was evaluated by 15 students of 2nd semester acting as high school pupils by using questionare. All six students were evaluated having clear and loud voice but lack of ability to motivate their pupils to learn. Most students stayed closely with PPT slides. Students also had difficutly to manage the time so teaching closure and evaluation could not be done.